Erdafitinib treatment in metastatic urothelial carcinoma: a real-world analysis - Rouvinov, Keren; Levanon, Eran; Peer, Avivit; Sarfaty, Michal; Sarid, David; Neiman, Victoria; Grikshtas, Eduard; Rosenbaum, Eli; Kushnir, Igal; Talmor, Barak; Friger, Michael; Zarbiv, Yonaton; et al. (Frontiers in Oncology, 2023)
Abstract Background: Erdafitinib, a fibroblast growth factor receptor (FGFR) inhibitor is a standard post chemotherapy advanced treatment line for metastatic urothelial carcinoma harboring FGFR2/3 genomic alterations. It was approved based on a phase 2 clinical trial, revealing a 40% response rate, and 13.8 months overall survival. These FGFR genomic alterations are uncommon. Thus, real-world data on erdafitinb use is scant. We herein describe erdafitinib treatment outcome in a real world patient cohort. Methods: We retrospectively reviewed the data of patients treated with erdafitinib from 9 Israeli medical centers. Results: Twenty-five patients with metastatic urothelial carcinoma (median age 73, 64% male, 80% with visceral metastases) were treated with erdafitinib between January 2020 to October 2022. A clinical benefit (complete response 12%, partial response 32%, stable disease 12%) was seen in 56%. Median progression-free survival was 2.7 months, and median overall survival 6.73 months. Treatment related toxicity ≥ grade 3 occurred in 52%, and 32% discontinued therapy due to adverse events. Conclusions: Erdafitinib therapy is associated with a clinical benefit in the real world setting, and associated with similar toxicity as reported in prospective clinical trials.